Hubungan Konseptual antara Candi-candi di Jawa Timur dengan Pura di Bali - Setiawan, I Ketut (Jurnal Kajian Bali (Journal of Bali Studies), 2016)
Abstract Bali has contacted with Java in a long period of time in terms of historical and cultural aspects. Based on those historical and archeological evidences, it can be understood  that the Balinese clasical kingdoms had contacted with Java, particularly with the Middle and East Java kingdoms from the 8th Century. Those relations had been strengthened  in the 10th to 11th Century, especially in the reign of Udayana King, who married with a princesses from East Java, Gunapriya Dharmapatni. The impacts of those relations, we can see in terms of political and cultural aspects in the present day Bali. One of these impacts, we can see in the similar forms and functions between the East Java and the Balinese temples.
Keywords: conceptual relation, temple (Candi), Pura, East Java, Bali